2020
DOI: 10.15376/biores.15.2.2471-2482
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fungicidal effects of post-culture medium of selected mold fungi and bacteria in relation to Basidiomycetes fungi, causing wood destruction

Abstract: The results of the post-culture fungicidal medium from Trichoderma viride Pers. and Alternaria alternata (Fr.) Keissl. mold fungi and Acetobacter xylinum bacteria were studied relative to selected fungi belonging to Basidiomycetes, which cause wood decay. The obtained results confirmed that post-culture liquids derived from the cultivation of various microorganisms might have a differentiated fungicidal effect on wood-decaying fungi. The lowest concentration of fluid from A. xylinum culture added to the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Thus far, there have been no available data in the literature on the effectiveness of protecting softwood or hardwood with SCOBY extracts or microorganisms. Research by Betlej et al (2020), carried out as a nutrient test, confirm the ability of the liquid from A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, there have been no available data in the literature on the effectiveness of protecting softwood or hardwood with SCOBY extracts or microorganisms. Research by Betlej et al (2020), carried out as a nutrient test, confirm the ability of the liquid from A.…”
Section: Resultsmentioning
confidence: 99%
“…The killing properties of fermented kombucha drinks against dangerous pathogens, such as Staphylococcus aureus, Shigella sonnei, Escherichia coli, Aeromonas hydrophila, Yersinia enterocolitica, Pseudomonas aeruginosa, Enterobacter cloacae, Staphylococcus epidermis, Campylobacter jejuni, Salmonella enteritidis, Salmonella typhimurium, Bacillus cereus, Helicobacter pylori, and Listeria monocytogenes have been studied by Sreeramulu et al (2000). The fungicidal properties of the post-culture medium from A. xylinum bacteria were observed by Betlej et al (2020). Researchers found that small amounts of bacterial post-culture medium are sufficient to completely inhibit the growth of fungi that cause deep wood decay.…”
Section: Introductionmentioning
confidence: 99%
“…Sample A contained more bacteria than sample B, which benefitted the generation of flavor substances. [ 29 ] In addition, sample A contained more saccharifying mycete than sample B, leading to better saccharification efficiency. Combined with the research in the previous paragraph, E. cristatum could benefit the quantity and species of other microorganisms, which conforms to the precondition of cofermentation.…”
Section: Resultsmentioning
confidence: 99%
“…In this process, fungi in a mold culture (also called Daqu in China) hydrolyze the starch present in five grains (glutinous rice, sorghum, maize, wheat, and rice) into reducing sugars, and Saccharomycetes in the mold culture subsequently transform reducing sugars into alcohol; then, bacteria in the mold culture produce various flavoring substances during Wuliangye liquor fermentation. [2] Therefore, the saccharification efficiency, yield, and quality improve during the production of Wuliangye liquor. [3] DOI: 10.1002/star.202200236 Saccharification efficiency can be improved in two ways: optimizing the saccharification process and enhancing the microorganisms in mold cultures.…”
Section: Introductionmentioning
confidence: 99%